2014
DOI: 10.1192/bjp.bp.113.127886
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum morphology in first-episode and chronic schizophrenia: combined magnetic resonance and diffusion tensor imaging study of Chinese Singaporean patients

Abstract: Morphological abnormalities in the corpus callosum may increase with illness progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
9
40
0
Order By: Relevance
“…In the Arnone, et al meta-analysis, first episode patients were more likely to have decreased corpus callosum areas, and chronic patients were more likely to demonstrate an increase in area (Arnone et al, 2008). A more recent study of first-episode and chronic schizophrenia patients found decreased corpus callosum area and volume in all patients, but in comparing first-episode and chronic patients reported that chronicity contributed to greater decrease in four of five corpus callosum area segments; in fact, this particular study reported that first-episode patients only differed from healthy controls in two of five area regions (Collinson et al, 2014). One longitudinal study of the corpus callosum in adult-onset chronic schizophrenia patients demonstrated progressive decline in collosal size, with poor-outcome patients demonstrating more pronounced decline (Mitelman et al, 2009).…”
Section: 2 Structural Neuroimagingmentioning
confidence: 85%
“…In the Arnone, et al meta-analysis, first episode patients were more likely to have decreased corpus callosum areas, and chronic patients were more likely to demonstrate an increase in area (Arnone et al, 2008). A more recent study of first-episode and chronic schizophrenia patients found decreased corpus callosum area and volume in all patients, but in comparing first-episode and chronic patients reported that chronicity contributed to greater decrease in four of five corpus callosum area segments; in fact, this particular study reported that first-episode patients only differed from healthy controls in two of five area regions (Collinson et al, 2014). One longitudinal study of the corpus callosum in adult-onset chronic schizophrenia patients demonstrated progressive decline in collosal size, with poor-outcome patients demonstrating more pronounced decline (Mitelman et al, 2009).…”
Section: 2 Structural Neuroimagingmentioning
confidence: 85%
“…In these cross-sectional studies, it was found that WM deficits in first-episode patients were either absent or less severe than in the multi-episode patients (Collinson et al, 2014; Friedman et al, 2008; Kong et al, 2011). Several studies have found greater FA decline with increasing age in schizophrenia patients, compared to healthy controls, from young-adulthood to late adulthood (reviewed by Peters et al (Peters et al, 2010)), which would be consistent with the model that includes decline after illness onset (i.e.…”
Section: White Matter Development In Schizophreniamentioning
confidence: 98%
“…DTI studies have produced evidence for WM abnormalities in first-episode patients (Cheung et al, 2011; Douaud et al, 2009; Luck et al, 2011; Peters et al, 2010; Rathi et al, 2011; Wang et al, 2011) and chronic patients (Konrad and Winterer, 2008), though findings are less consistent in the first-episode group. A significant portion of studies have shown no differences between first-episode patients and healthy individuals (Kong et al, 2011; Mulert and Scarr, 2012; Peters et al, 2010), while whole brain voxel-based analyses tend to produce positive findings and fiber tracking or region-of-interest analyses more often indicate no abnormalities (Collinson et al, 2014; Kong et al, 2011; Mulert et al, 2012; Peters et al, 2010). One factor that might contribute to the conflicting results is variability in medication status and symptom history, even in those individuals relatively early in the illness.…”
Section: White Matter Development In Schizophreniamentioning
confidence: 99%
“…In fact, it has been previously reported that callosal connections are altered in the brain of patients with schizophrenia, especially via reduction of the connection between the hemispheres [4]. It has also been reported that the volume of the corpus callosum, where the myelinated axons of the callosal projection neurons are located, is reduced in schizophrenia [27][28][29]. There is a possibility that FILIP is involved in the pathogenesis of schizophrenia through the reduction of cortico-cortical connections.…”
Section: Discussionmentioning
confidence: 99%